2014
DOI: 10.3892/mmr.2014.2321
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin identified by comparative mass-spectra analysis is a potential marker for invasive progression of hepatocellular carcinoma

Abstract: Abstract. At present, the diagnosis and prognosis of hepatocellular carcinoma (HCC) metastasis remains poor. Recently, a number of proteins associated with the metastasis and invasion of HCC were identified; however, the effective markers require further elucidation. In the current study, a nucleolin expression was observed in MHCC97L and HCCLM9 HCC cell lines, with low and high metastatic potentials respectively, using comparative proteomics. The data indicated that nucleolin expression in the nucleus was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…38). Further studies have strengthened the case for use of nucleolin as a marker for invasive HCC progression and suggest it may have role in the process of transcriptional elongation (39). It has also been shown that nucleolin positively regulates EGFR stability by binding to and interacting with EGFR mRNA, thereby promoting EGFinduced malignant cell transformation and migration (40).…”
Section: Discussionmentioning
confidence: 97%
“…38). Further studies have strengthened the case for use of nucleolin as a marker for invasive HCC progression and suggest it may have role in the process of transcriptional elongation (39). It has also been shown that nucleolin positively regulates EGFR stability by binding to and interacting with EGFR mRNA, thereby promoting EGFinduced malignant cell transformation and migration (40).…”
Section: Discussionmentioning
confidence: 97%
“…Nucleolin (NCL) is a potential target for cancer therapy. NCL is involved in the control of RNA and DNA metabolism, and its overexpression promotes the proliferation and survival of cancer cells as well as boosts tumorigenesis by promoting tumor invasion and angiogenesis, which has attracted more and more attention recently. , A variety of methods have been reported to detect NCL including colorimetry, electrochemiluminescence, mass spectrum, and so on. In addition, commercial NCL detection assay kits are mainly based on the method of ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] The mechanisms underlying this association may include regulation of cancer cell proliferation, apoptosis, angiogenesis, invasion and metastasis. 8,9,[18][19][20][21][22][23][24][25] Thus, NCL may be a promising target for anti-tumor therapy, and in recent years, progress has been made in aptamers, polypeptides and immune agents targeting NCL. 8,9,[26][27][28][29][30] The role of NCL in EC has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%